IMPROVING STUDENTS’ SPEAKING ABILITY UNDER TOTAL PHYSICAL RESPONSE AT CLASS VII OF SMP NEGERI 8 KENDARI - Netty Huzniati Andas (Journal of English Education, 2016)
The reason to conduct this study was to improve student’s speaking ability at class VII A in SMPN 8 Kendari by using Total Physical Response Technique. There were 24 students as the subject of this study. This study applied Action Research which involved planning, action, observation, and reflection. The researcher designed three cycles to see the students’ improvement in speaking ability. To get accurate data, the researcher used four kinds of instruments such as speaking test, observation sheet, tape recorder, and note taking. Analytical and statistical analysis was used to measure the students’ speaking ability. In analytical analysis the researcher examined what found in observation sheet and note taking. While, in statistical analysis the researcher calculated what found in students’ speaking test. After analyzing the data, this research found that there was a significant improvement on students’ speaking ability under TPR. It was indicated by the students’ criteria of success 65% was achieved. It also found that under TPR students were not afraid to express their idea anymore, they seemed to enjoy the activity as they understand how to be an instructor and performer, and the students more active to participate all the activity in classroom.